P-014 Volume-of-interest cone-beam CT imaging with reduced radiation dose of cerebral aneurysms treated with flow diverter. (22nd July 2018) - Hiramatsu, M; Sugiu, K; Hishikawa, T; Nishihiro, S; Kidani, N; Takahashi, Y; Murai, S; Date, I
Abstract : Background and purpose: Contrast enhanced cone-beam CT imaging has been increasingly used for the assessment of vessel structures and implanted devices in endovascular procedures. However, long scan time increases radiation exposure. A new 'Volume of Interest' cone-beam CT prototype software (VOI CBCT) with low-dose acquisition technology was developed to overcome this problem. The aim of this study was to assess image quality of VOI CBCT images in comparison with conventional CBCT images in cases of cerebral aneurysms treated with flow diverter placement. Method: Patients treated with a flow diverter for an internal carotid artery aneurysm were enrolled in this study. Patients received both conventional CBCT acquisition and VOI CBCT acquisition with intra-arterial injection of 20% contrast medium during the procedures. VOI CBCT reconstruction algorithm was applied to the acquired VOI data in order to compensate for missing information due to the collimation. Image quality was independently evaluated in each case using a five-point scale by two physicians experienced in neuro-endovascular therapy. The physicians rated the overall image quality, as well as dedicated image quality measures of stent struts visibility, stent apposition to the vessel, parent artery, branch of parent artery, aneurysm, bone structure and brain parenchyma. The reduction of equivalent radiation dose was assessed with five fluorescence glass dosimeters placed around each eye position on a head phantom. Results: A total of 10 patients were enrolled in this study. The VOI CBCT and conventional CBCT images were successfully obtained for all patients. The median overall image quality score for VOI CBCT showed no significant difference compared with that of conventional CBCT (p>0.05). For the dedicated image quality measures, there were no significant differences between the ratings for VOI CBCT and conventional CBCT. The equivalent radiation dose for eye lens by conventional CBCT (22.49 mSv) was significantly reduced compared to VOI CBCT (0.97 mSv, p<0.05). Conclusion: This study suggested that the VOI CBCT prototype software could reduce radiation dose without changing image quality in comparison with conventional CBCT in cases of cerebral aneurysms treated with flow diverter placement. Disclosures: M. Hiramatsu: 1; C; SIEMENS Healthneers Japan. K. Sugiu: 1; C; Siemens Healthiness Japan. T. Hishikawa: None. S. Nishihiro: None. N. Kidani: None. Y. Takahashi: None. S. Murai: None. I. Date: None.